PROSPECÇÃO DE METABÓLITOS BIOATIVOS PROVENIENTES DE MICROALGAS EXTREMÓFILAS: APLICAÇÕES NA ÁREA DA SAÚDE. - SOUSA, Pedro Felipe Rodrigues (2021)
Microalgae are eukaryotic microorganisms capable of using autotrophic and heterotrophic pathways in their metabolism. These can be found in the most diverse types of aquatic environments. Certain types of environments have extreme conditions to which organisms adapt to survive. These adaptations induce specializations and activation of secondary metabolic pathways capable of producing compounds that allow organisms to survive in the most varied conditions. Several of these secondary metabolites have activities against microorganisms due to media competition, antibiofilm, antioxidant activity, among others. Thus, this work sought to evaluate the biotechnological potential in health, using in silico prospecting techniques, of two green microalgae Chlamydomonas acidophila and Jaagichlorella hainangensis. Both microalgae were isolated from extremophile environments located in a mining area: Chlamydomonas acidophila from an acidic copper mine drainage and Jaagichlorella hainangensis from a natural iron lake. After the steps of obtaining the genomes, quality control and assembly, they were annotated using the GenSAS platform. To predict gene clusters linked to secondary metabolites, the antiSMASH platform was used in the bacterium and fungus versions. AntiSMASH pointed to several gene clusters linked to biosynthetic pathways of secondary metabolites of interest in both microalgae such as terpenes, siderophores and ectoins. The results of these predicted clusters were analyzed using synthesis plots with the groupings deposited in the MIBiG and the possible functions of the genes were predicted through BLAST in the CDD and in the PFAM database. AntiSMASH also identified clusters classified as non-ribosomal synthase peptides (NRPS) and polyketide synthases (PKS) in the genome of the two microalgae and NRPS / PKS hybrid clusters only in Jaagiclhorella hainangensis. Genes related to PKS type I were the most prevalent in Jaagichlorella hainangensis, followed by genes related to type III. However, this profile is not found in Chlamydomonas acidophila in which only genes related to PKS type III have been identified. More robust analyzes with the NRPS and PKS clusters predicted in the genomes of these microalgae were performed using the NaPDoS platform. Only in Jaagichlorella hainangensis 2 clusters were linked with low similarity to biosynthetic pathways, one of which is a PKS cluster similar to the epothilone sequence, a metabolite already known for its anticancer activity. The lack of results in Chlamydomonas acidophila and in the remaining clusters in Jaagichlorella hainangensis indicate that these sequences may be related to pathways that are not categorized or not inserted in NaPDoS and in these cases are linked to compounds of unprecedented character. Obtaining these preliminary data in these species, direct possible in vitro experiments which can be carried out with the objective of extracting secondary metabolites as well as elucidating metabolic pathways, in addition to contributing to genomic databases with the predicted gene clusters for possible syntenic relationships and expansion of the genomic knowledge of microalgae.